Genetic markers of the proliferative syndrome in age-related macular degeneration and chronic angle-closure glaucoma - L. M. Balashova; N. A. Bakunina; A. A. Fedorov; Yu. D. Kuznetsova; A. V. Popov; M. E. Viner (Российский офтальмологический журнал, 2023)
Purpose: clinical and genetic research of primary chronic angle-closure glaucoma (PACG) and age-related macular degeneration (AMD) for prospective pathogenetically-oriented targeted treatment of these condition.Materials and methods. 15 patients with isolated ocular proliferative syndrome were divided into 2 groups depending on their diagnosis: 1) 7 patients (14 eyes) aged 55 to 83 with confirmed wet AMD (4 women and 3 men). 2) 8 patients (16 eyes) aged 45 to 80 with chronic PACG (5 women and 3 men). The patients were followed up for 1 to 3 years.Results. In both conditions, we found mutations in the genes of the Russian population involved in the process of proliferation: VEGF A, CFH, and COL11A1. We developed an algorithm of bioinformatic analysis of full-exome/full-genome sequencing data which takes account of the aggregate of clinical and genetic data and helps refine the prognosis of the course of proliferation. Genetic markers remain unchanged throughout the patient’s life, so it is important to conduct these studies in old age.Conclusion. To prevent the proliferative syndrome in patients with chronic PACG and AMD, and develop individual targeted pathogenetic therapy schemes for these diseases, specialized molecular genetic tests are needed, the results of which could be analyzed with the developed algorithm.